Technological Advances in Preclinical Drug Evaluation: The Role of -Omics Methods - Pavelić, Sandra Kraljević; Markova-Car, Elitza; Klobučar, Marko; Sappe, Lana; Spaventi, Radan (Current Medicinal Chemistry, 2020)
Preclinical drug development is an essential step in the drug development process where the evaluation of new chemical entities occurs. In particular, preclinical drug development phases include deep analysis of drug candidates’ interactions with biomolecules/targets, their safety, toxicity, pharmacokinetics, metabolism by use of assays in vitro and in vivo animal assays. Legal aspects of the required procedures are well-established. Herein, we present a comprehensive summary of current state-of-the art approaches and techniques used in preclinical studies. In particular, we will review the potential of new, -omics methods and platforms for mechanistic evaluation of drug candidates and speed-up of the preclinical evaluation steps.
Keywords: mass spectrometry